Early Childhood Education of the Foreign Child/Student - a Normative Approach - Iwona Samborska (Maria Curie-Skłodowska University, Lublin, Poland, 2023)
Introduction: The aim of the article is to discuss legal solutions concerning the functioning of a foreign child in the space of elementary education. The object of analysis is the legal norms included in the texts of legal acts in the system of universally binding national law in the area of education and care of foreign children in primary education. Research Aim: The research objective is to analyse, interpret and evaluate the formal-legal basis of the functioning of the child/student - foreigner in the space of elementary education. Evidence-based Facts:In studies on the legal empowerment of the foreign child/student in the Polish education system, there is a lack of analyses focusing on the initial stages of education. What is missing in this respect is a thorough analysis of the legal regulations constituting the basis for activities in the area of early childhood education. Summary: The article identifies and discusses the current legal solutions constituting the basis for the functioning of a foreign child/student in the space of elementary education. It analyses and interprets the legal regulations in the system of internal (national) generally applicable law concerning education and care of foreign children. Legal institutions serving the realisation of the right to education and integration were presented. The scopes of legislative shortcomings and directions of necessary changes to improve the functioning of foreigners in the are a of early childhood education are indicated.